The Chronic Migraine Brain: What Have We Learned From Neuroimaging? - Filippi, Massimo; Messina, Roberta (Frontiers in Neurology, 2020)
Chronic migraine is a highly disabling disease with a great impact on socioeconomic functioning and quality of life of migraine patients. Chronic migraine usually evolves from episodic migraine that gradually increases in attack frequency, supporting the view of migraine as a spectrum disorder. Pathophysiological mechanisms responsible for migraine chronification are not fully understood. Likewise episodic migraine, chronic migraine patients showed widespread functional and structural alterations of cortical and subcortical pain-related brain areas. However, chronic migraine patients experience a more pronounced dysfunction of the pain inhibitory network and an increased sensitization of the central pain pathways, which might explain the higher susceptibility to migraine attacks. Imaging studies have highlighted that brain regions with a key role in migraine attack generation, like the pons and hypothalamus, might also be involved in migraine chronification. Whether brain alterations are biomarkers that predispose migraine patients to chronification or reflect adaptive or maladaptive responses to the increasing headache frequency is still a matter of debate. The central mechanisms of action of chronic migraine preventive treatments and imaging biomarkers that could predict patients’ treatment response have also been explored. In this new era of migraine treatments, a better understanding of chronic migraine pathophysiology will pave the way for the development of new improved treatments specifically designed for chronic migraine patients.